Justification for the Olympic Reform Package Based on Good Practice - Csiza, Marton (International Journal of Engineering and Management Sciences, 2022)
The Olympic Games have always been the pinnacle of sport and achievement. The modern Olympics are held every four years, and the venue is chosen from among the cities that apply. In my research, I wanted to find out the reasons for the decline in the popularity of the Games. To answer this question, I looked at 2 successful Olympics (2000 Sydney, 2012 London) in the hope of identifying success factors that could be adapted to other host countries. I conducted secondary research, reviewed related international and national research, and the available economic data. During the document analysis, I found that the expected costs of organising the Olympic have increased significantly over the last two to three decades, and under-planning is a common feature. As a result of the research, I have found that the most important pillars of successful organisation are a proper organising committee, comprehensive opportunity and risk analysis, accurate planning, sustainability in planning, continuous cost control, private sector support, and the work of volunteers.